2018
DOI: 10.1001/jamacardio.2017.4572
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Findings in National Basketball Association Athletes

Abstract: Despite the improved specificity of the international recommendations over previous athlete-specific ECG criteria, abnormal ECG classification rates remain high in NBA athletes. The development of left ventricular concentric remodeling appears to have a significant influence on the prevalence of abnormal ECG classification and repolarization abnormalities in this athlete group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 17 publications
(54 reference statements)
2
28
2
1
Order By: Relevance
“…In a recent study of 519 National Basketball Association athletes' ECGs, early repolarization referred as convex ST segment elevation and T wave inversion in V2-V4 leads was the most frequent finding in black / African players. In the same study it was mentioned that abnormal findings were more prevalent in older athletes suggesting a possible correlation between long term high intensity training and ECG abnormalities [6]. In our case, ECG showed sinus bradycardia and ST segment changes that were in consistence with the above data.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study of 519 National Basketball Association athletes' ECGs, early repolarization referred as convex ST segment elevation and T wave inversion in V2-V4 leads was the most frequent finding in black / African players. In the same study it was mentioned that abnormal findings were more prevalent in older athletes suggesting a possible correlation between long term high intensity training and ECG abnormalities [6]. In our case, ECG showed sinus bradycardia and ST segment changes that were in consistence with the above data.…”
Section: Discussionsupporting
confidence: 87%
“…International consensus has established standards of ECG interpretation in athletes and provided guidance on further testing and clinical evaluation of athletes (Sharma et al, ). Recent application of these international ECG criteria to differing athlete populations has yielded findings of abnormal ECG as low as 3% (Dhutia et al, ) and up to 15.6% (Waase et al, ) of those tested, a discrepancy that highlights knowledge gaps in understanding of the continuum of sex‐, race‐, and age‐specific characteristics of electrophysiological (EP) substrate in athletes (Heidbuchel, ). The vectorcardiogram (VCG) provides additional information to routine 12‐lead ECG evaluation (Waks et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Improved accuracy was seen with the International Criteria versus the Seattle Criteria in National Basketball Association players, though 15.8% of African-American and 11.5% of white athletes still had abnormal ECGs with no imaging evidence of cardiac disease 49. Another study of almost 5000 athletes showed only 3.0% had an abnormal ECG with the new criteria, which was a 50% reduction compared with the Seattle Criteria 50.…”
Section: Resultsmentioning
confidence: 93%